Skin & Menopause - Sudhaa Sharma; Sana Bashir; Vishal R Tandon; Annil Mahajan (Dr. Annil Mahajan, 2023)
Aging is a natural process and not a disease that all living organisms go through, as they grow older and accumulate cellular damage over time. The desire to maintain a beautiful, youthful appearance crosses all racial, cultural, and economic boundaries. A component of beauty may include a retained youthfulness despite advancing age, by the appearance of smooth, even skin complexion and the absence of wrinkles, and skin laxity.